The nurse's role as operational manager of the primary health care unit in the Maré Complex, Rio de Janeiro (RJ) (Research, Society and Development, 2024)
This exploratory and applied study, with a qualitative approach, aimed to identify the main difficulties/challenges faced by nursing professionals in the operational management of the Primary Health Care (PHC) in the Maré Complex, Rio de Janeiro (RJ). Through interviews with nurses from three of the seven health units in the region, the need for improvement in communication, establishment of common goals, and professional training was identified. Violence in the area also emerged as a critical challenge, requiring public policies and specific strategies to ensure safety and access to health. The results highlight the need for improvements in the management of Primary Health Care (PHC), emphasizing effective communication, common goals, regular team meetings, and professional training. The importance of investment in infrastructure, identified as a positive aspect, and innovation to overcome challenges in service quality is also emphasized. It is recognized that the results obtained are specific to the Maré Complex and may not be fully applicable to other regions.